Competency Components for Trainers in Workplaces Collaborating with Higher Education Institutions: Confirmatory Factor Analysis (CFA) Technique - Chimparos, Suranat; Sisan, Boonchan; Tungkunanan, Pariyaporn (Journal of Technical Education and Training, 2025)
This research aims to identify and establish the fundamental competency components necessary for trainers in workplace settings that collaborate with higher education institutions in Thailand. These trainers play the key role in connecting academic knowledge with practical application, significantly improving the effectiveness of Work-Integrated Learning (WIL) programs. A quantitative research design was utilized, involving 800 participants from five stakeholder groups: university administrators, curriculum instructors, career support staff, enterprise managers, and in-company trainers. Stratified random sampling guaranteed representation among numerous institutional varieties. Strong content validity and high reliability were obtained by the research instrument, which was developed through an extensive literature review and expert consultation. Confirmatory Factor Analysis (CFA) was utilized to determine the construct validity of the suggested competency model. As a result, the model indices showed exceptional outcomes. The findings confirmed three key competency domains: (1) knowledge competencies, such as curriculum quality development, training material design, and understanding of industrial laws; (2) skill competencies, such as digital media use, problem-solving, and communication skills; and (3) attitude competencies, such as work ethics, responsibility, and social interaction. These findings emphasize the necessity of building trainer competencies that are aligned with the changing needs of the industry, as well as the usefulness of educational-industry partnerships in preparing learners for the real world.